Elucidating the Role of Virulence Traits in the Survival of Pathogenic E. coli PI-7 Following Disinfection - Sivakumar, Krishnakumar; Lehmann, Robert; Rachmadi, Andri Taruna; Augsburger, Nicolas; Zaouri, Noor; Tegner, Jesper; Hong, Pei-Ying (Frontiers in Bioengineering and Biotechnology, 2020)
Reuse and discharge of treated wastewater can result in dissemination of microorganisms into the environment. Deployment of disinfection strategies is typically proposed as a last stage remediation effort to further inactivate viable microorganisms. In this study, we hypothesize that virulence traits, including biofilm formation, motility, siderophore and curli production along with the capability to internalize into mammalian cells play a role in survival against disinfectants. Pathogenic E. coli PI-7 strain was used as a model bacterium that was exposed to diverse disinfection strategies such as chlorination, UV and solar irradiation. To this end, we used a random transposon mutagenesis library screening approach to generate 14 mutants that exhibited varying levels of virulence traits. In these 14 isolated mutants, we observed that an increase in virulence traits such as biofilm formation, motility, curli production and internalization capability, increased the inactivation half-lives of mutants compared to wild-type E. coli PI-7. In addition, oxidative stress response and EPS production contributed to lengthening the lag phase duration (defined as the time required for exposure to disinfectant prior to decay). However, traits related to siderophore production did not help with survival against the tested disinfection strategies. Taken together, the findings suggested that selected virulence traits facilitate survival of pathogenic E. coli PI-7, which in turn could account for the selective enrichment of pathogens over the non-pathogenic ones after wastewater treatment. Further, the study also reflected on the effectiveness of UV as a more viable disinfection strategy for inactivation of pathogens.